El Viatge : Accions - Espai 10 - Instal-lacions : Fundació Joan Mir´1982-1983. - Fundacio Joan Miro, Barcelona (Barcelona : Fundació Joan Miró, 1982)
Von Schaewen, Deidi ; Amat, Frederic ; Buades, Miguel ; Cardells, Joan ; Droste, Monika ; Duran Esteva, Pep ; Ferrer, Benet ; Gibert, Sara ; Katase, Kazuo ; Kutscher, Vollrad ; Lauwaert, Yvette ; Llabrés, Joan ; Llimos, Robert Nininger, Nicola Susan ; Noguera ; Uclés, Josep ; Wenders, Wim ; Terrades, Andreu ; Caillol, Claude ; Perejaume ; Cuin, Noël ; Navarro, Miquel
2 boekjes (geniet) ; 9 vouwbladen
boek